2013
DOI: 10.3389/fpsyg.2013.00299
|View full text |Cite
|
Sign up to set email alerts
|

A New Measure of Interpersonal Exploitativeness

Abstract: Measures of exploitativeness evidence problems with validity and reliability. The present set of studies assessed a new measure [the Interpersonal Exploitativeness Scale (IES)] that defines exploitativeness in terms of reciprocity. In Studies 1 and 2, 33 items were administered to participants. Exploratory and Confirmatory Factor Analysis demonstrated that a single factor consisting of six items adequately assess interpersonal exploitativeness. Study 3 results revealed that the IES was positively associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…For example, people high in psychological entitlement, interpersonal exploitativeness, and/or dispositional greed make more competitive and fewer cooperative choices in resource allocation tasks, such as the commons dilemma and the dictator game. These competitive choices result in greater gain for the selfish person in the short term, to the detriment of others (Brunell et al 2013, Seuntjens et al 2015.…”
Section: Benefits Of Selfish Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, people high in psychological entitlement, interpersonal exploitativeness, and/or dispositional greed make more competitive and fewer cooperative choices in resource allocation tasks, such as the commons dilemma and the dictator game. These competitive choices result in greater gain for the selfish person in the short term, to the detriment of others (Brunell et al 2013, Seuntjens et al 2015.…”
Section: Benefits Of Selfish Motivationmentioning
confidence: 99%
“…Self-interest is at best a weak predictor of attitudes and behavior (Sears & Funk 1990). Although some people are self-interested most of the time (Brunell et al 2013), and some situations tend to elicit selfinterested behavior and motivations in many people (Li et al 2013), people are also capable of acts of kindness, generosity, and compassion (for reviews, see Mikulincer & Shaver 2010). Humans, like other mammals, have an evolved caregiving system that promotes and motivates caring for their young, who are incapable of surviving on their own.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although other important work relies on hypothetical dilemmas, it is still the most akin to behavior that currently exists. These studies have found that narcissism is associated with less contributions to the common good in a resource dilemma game (Brunell et al, 2013;Campbell et al, 2005).…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%
“…These studies found that narcissism (especially narcissistic exploitativeness) was associated with a greater tendency to harvest more natural resources (i.e., forests) in hypothetical resource dilemma games, which in turn, depleted these resources for the larger community (Brunell et al, 2013;Campbell, Bush, Brunell, & Shelton, 2005). In other words, more narcissistic people behaved more selfishly and less prosocially in these games.…”
mentioning
confidence: 99%